A Review on Bacillus subtilis and Related Bacilli in Wastewater Treatment: Biofilm Formation, Genetic Regulation, and Industrial Pollutant Degradation - Hussein, Noor Nihad Abdul; Al-Saeedi, Bayan Shakir Mahmood; Jasim, Hiba A. (American Journal of Biology and Natural Sciences, 2026)
The global water scarcity crisis and the growing complexity of industrial effluents call for the development of resilient, self-sustaining bioremediation technology. Bacillus subtilis and its phylogenetically close representatives have been casted among the best characterisation candidates in wastewater treatment, owing to their capacity to generate robust biofilms and exhibit metabolic versatility. In this review, we will examine the molecular processes that dictate biofilm structure, with a focus on the EPS matrix, TasA amyloid fibers, and BslA hydrophobins. In this review, we discuss genetic circuitry that regulates the transition from planktonic to sessile lifestyles including the Spo0A (general response regulator)- and DegS-DegU (two-component system)-mediated systems. Additionally, It provides the degradation pathways of recalcitrant organic compounds and the immobilization of heavy metals. To meet the requirements of the relatively new industrial scale applications, we investigate the now fused fields of genetic engineering and nanotechnology. This review cites a total of 40 references in Vancouver style and provides a comprehensive overview of the current status of environmental biotechnology based on Bacillus.